Wild faith ebook How the christian right is taking over america. - Lavin, Talia (2024)
Esquire Best Nonfiction Books of 2024 The acclaimed author of Culture Warlords investigates the rise of the Christian Right over the last half-century that lays out the grim vision evangelicals are enforcing on our democracy. All across America, a storm is gathering: from book bans in school libraries to anti-trans laws in state legislatures; firebombings of abortion clinics and protests against gay rights. The Christian Right, a cunning political force in America for more than half a century, has never been more powerful than it is right now—it propelled Donald Trump to power, and it won’t stop until it’s refashioned America in its own image. In Wild Faith, critically acclaimed author Talia Lavin goes deep into what motivates the Christian Right, from its segregationist past to a future riddled with apocalyptic ideology. Using primary sources and firsthand accounts, Lavin introduces you to “deliverance ministers” who carry out exorcisms by the hundreds; modern-day, self-proclaimed prophets and apostles; Christian militias, cults, zealots, and showmen; and the people in power who are aiding them to achieve their goals. Along the way, she explores anti-abortion terrorists, the Christian Patriarchy movement, with its desire to place all women under absolute male control; the twisted theology that leads to rampant child abuse; and the ways conspiracy theorists and extremist Christians influence each other to mutual political benefit. From school boards to the Supreme Court, Christian theocracy is ascendant in America—and only through exploring its motivations and impacts can we understand the crisis we face. In Wild Faith, Lavin fearlessly confronts whether our democracy can survive an organized, fervent theocratic movement, one that seeks to impose its religious beliefs on American citizens.